Bubalus bubalis: A Short Story - Minervino, Antonio Humberto Hamad; Zava, Marco; Vecchio, Domenico; Borghese, Antonio (Frontiers in Veterinary Science, 2020)
The domestic buffalo (Bubalus bubalis), also known as water buffalo or Asian buffalo to prevent confusion with the American bison (Bison bison), and wrongly named buffalo in North America, comprises two subspecies: the river buffalo (B. bubalis bubalis) and the swamp buffalo (B. bubalis kerabau). The swamp buffalo has a consistent phenotype and is considered as one type, even if many breeds are recognised within it; conversely, the river buffalo subspecies has many breeds. We found limited information available regarding the worldwide distribution of buffaloes. The best estimate is that 208,098,759 buffalo head are distributed in 77 countries in five continents. In this review, we presented the basic aspects of the water buffalo and unravelled the buffalo path followed from the origin of the species to its current global distribution. We reviewed several data sources to provide a better estimate of the world buffalo count and distribution.